The Effect of Audit Quality, Firm Size, and Auditor Reputation on Earnings Management: A Study of Manufacturing Companies Listed on the Indonesian Sharia Stock Index (ISSI) for the Period 2019-2023) - Khusna Lathifannisa; Evi Ekawati; Ahmad Hazas Syarif (Manunggal Halim Jaya, 2026)
This study examines the effect of audit quality, firm size, and auditor reputation on earnings management in manufacturing companies listed on the Indonesian Sharia Stock Index (ISSI) during 2019–2023. Using a quantitative approach with purposive sampling, 20 companies were analyzed using secondary data from annual financial reports. Panel data regression with the Common Effect Model was applied. The partial t-test results show that audit quality has a negative and significant effect on earnings management (coefficient = -0.293686, t-statistic = -4.545122, p-value = 0.0000), firm size has a negative and significant effect (coefficient = -0.027295, t-statistic = -2.744986, p-value = 0.0072), and auditor reputation also has a negative and significant effect (coefficient = -0.244585, t-statistic = -3.796877, p-value = 0.0003). These results indicate that higher audit quality, larger firm size, and reputable auditors reduce earnings manipulation practices. From an Islamic business perspective, accurate and transparent financial reporting reflects the value of justice ('adl) as mandated in QS. Al-Maidah: 8, where fairness in disclosure is a form of moral and spiritual accountability to Allah SWT. This study supports signaling theory and provides practical implications for strengthening transparency, accountability, and Sharia-compliant practices.